THỰC TRẠNG DÙNG THUỐC GIẢM ĐAU SAU PHẪU THUẬT (Vietnam Journal of Community Medicine, 2021)
Objective: To describe the current situation of post-operation painkillers use at the general surgery department of Cai Nuoc General Hospital. Objects and methods: Cross-sectional descriptive study on 172 patients undergoing surgery at General Surgery Department, Cai Nuoc General Hospital. Results: Mainly using paracetamol for pain relief, accounting for 98.98%. For epidural painkillers (levobupivacaine and fentanyl), the rate of use decreased significantly when comparing group 1 with group 2. This difference was statistically significant (p